The role of epigenetics in plant pathogens interactions under the changing environments: A systematic review - Wenhao Wu; Guoqiang Fan (Plant Stress)
Epigenetic modifications are emerging as pivotal regulatory mechanisms in plant-pathogen interactions, especially under changing environmental conditions. This review systematically examines the application of epigenetic processes (DNA methylation, histone modifications, non-coding RNAs, and RNA methylation) in shaping the intricate dynamics between plants and pathogens. DNA methylation influences plant immunity by modulating gene expression and chromatin accessibility, while histone modifications, such as acetylation and methylation, enable plants to establish robust defenses by fine-tuning stress-responsive genes. Small RNAs (miRNAs) and long non-coding RNAs (lncRNAs) act as post-transcriptional regulators, orchestrating immune signaling and pathogen counter-defense strategies. RNA methylation, particularly N6-methyladenosine (m6A), adds another layer of regulation, controlling the stability and translation of transcripts involved in host immunity and pathogen virulence. The review highlights the co-evolutionary arms race between plants and pathogens, where pathogens manipulate host epigenetic machinery to suppress defenses, while plants deploy countermeasures to maintain immune resilience. Advances in high-throughput sequencing and CRISPR-based tools are shedding light on these complex interactions, offering opportunities to engineer crops with enhanced disease resistance. Furthermore, the review emphasizes the need to explore the interplay between these epigenetic mechanisms under multifaceted environmental stresses. By integrating recent findings, this review underscores the potential of epigenetic research to revolutionize crop protection strategies, ensuring agricultural sustainability in a rapidly changing world.